THE ROLE OF MORALS IN THE IMPLEMENTATION OF RELIGIOUS MODERATION - Baihaqi, Ahmad; Rosadi, Endang (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
The purpose of this study is to explore the role of morality in creating religious harmony and tolerance, in addition, the challenges and opportunities faced in the implementation of morality in the context of diversity. This approach focuses on interfaith dialogue that builds bridges of communication and mutual understanding, as well as respect for differences as elements that enrich social life. The methods applied in this study include literature review to explore relevant theories and concepts, as well as interviews with religious leaders and various members of society. Through this interview, it is hoped that a comprehensive perspective can be obtained regarding the application of morals in the practice of religious moderation, including the challenges faced and the successes that have been achieved. The results of the study show that the role of morality not only strengthens religious moderation but also encourages active community involvement in building a harmonious community. By prioritizing mutual respect and understanding, individuals from various religious backgrounds can work together in various aspects of social life. These findings emphasize the importance of moral education in the religious education curriculum as a foundation for sustainable moderation so that future generations are able to face the challenges of diversity with a constructive and inclusive attitude. This research emphasizes that morality plays an important role in religious moderation, encouraging tolerance, social harmony, and inclusive attitudes, so as to create a peaceful and balanced religious life in society.